Resistance of Several Varieties of Non-Tidal Lowland Paddy to Sheath Blight Disease Caused by Rhizoctonia solani - A. Muslim; Rinda Permatasari; A. Mazid (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Muslim et al. 2012. Resistance of Several Varieties of Non-Tidal Lowland Paddy to Sheath Blight Disease Caused by Rhizoctonia solani. JLSO 1(2):163-169. The use of high yielding varieties has increased paddy yields in non-tidal lowlands. However, paddy productivity often decreases due sheath blight disease caused  by Rhizoctonia solani. The objective of this study was to determine some non-tidal swamp rice varieties that are resistant to sheath blight. Response of paddy varieties to sheath blight  was evaluated in the screen house using micro-chamber screening method, with paddy variety as treatment.  Each treatment consisted of five varieties of paddy: Inpari13, Indragiri, Mekongga, Inpara3 and Ciherang. The result showed that all of the varieties were infected by R. solani.The lowest level of severity occurred in Inpara 3 with the average score of 38.88% whereas the highest severity occurred in Indragiri varietiy with the average score of 59.34%. Based on resistancy, none of the varieties tested showed resistant response. Moderately resistant response to sheath blight was indicated by Inpara 3, Mekongga, Ciherang (disease index 3.5-4.0); whereas  susceptible response was demonstrated by Inpari 13 and Indragiri (disease index 5.3-5.5). The average incubation period of the pathogen R. solani on Inpari 13, Indragiri and Mekongga was four days, Ciherang was five days and Inpara 3 was six days. Therefore, none of the five varieties of non-tidal lowland paddy tested in this reasearch was resistant to sheath blight disease caused by R. solani.